NIKAH SIRI DALAM PERSPEKTIF STRUKTURAL FUNGSIONAL - Arsal, Thriwaty (Forum Ilmu Sosial, 2012)
Nikah siri is not a new phenomenon in Indonesia, but based on positive law and Marriage Act 1974 violate norms despite siri marriage in Islam is a legitimate action in accordance with the terms valid throughout the wedding. The act of marriage siri is not   only done in certain circles, people with socio-economic and educational status of established, can not be separated from action siri marriage.  Negative implications posed by siri siri marriage but marriage still exist and flourish in society, because marriage siri functional for the culprit. various factors that shape a person to take action siri marriage, for example; strict rules state certified, and low levels of economic hardship, low education, knowledge of the concept of marriage, and personal experience.